Entrepreneurship in a "mature industry" (Center for Japanese Studies, University of Michigan, 1986)
This book introduce opening statement, stimulating and managing corporate entrepreneurship, the auto industry connection. Honda's approach to a mature industry. Entrepreneurship in he supplier industry...